Foams Emerging Technologies - Xu, Huijin; Yang, Chen; Jing, Dengwei (IntechOpen, 2020)
Foams are ubiquitous in human life and can be found in a variety of products and materials, such as sodas and sponges. There are liquid foams and solid foams, both of which have distinct properties useful for various applications. This book reviews, researches, and summarizes the potential uses of foam fluids and porous foams in engineering, medicine, and other industries. Chapters discuss different types of foams including multiphase foams, cellular foams, and ceramic foams as well as foam-generating mechanisms and techniques.